Autism spectrum disorder symptoms in children with ADHD: A community-based study. (December 2015) - Green, Jessica Leigh; Rinehart, Nicole; Anderson, Vicki; Nicholson, Jan M.; Jongeling, Brad; Sciberras, Emma
Highlights: Children with ADHD had elevated ASD symptoms relative to non-ADHD controls. ASD symptom severity was higher in boys than girls with ADHD. Greater ASD symptom severity was not associated with ADHD subtype. Greater ASD symptom severity was associated with greater ADHD symptom severity. Abstract: This study examined the prevalence of autism spectrum disorder (ASD) symptoms in a community-based sample of children with attention-deficit/hyperactivity disorder (ADHD) and non-ADHD controls. We also examined the relationship between ASD symptoms and ADHD subtype, ADHD symptom severity and child gender. Participants were 6–10-year-old children (164 ADHD; 198 non-ADHD control) attending 43 schools in Melbourne, Australia, who were participating in the Children's Attention Project. ADHD was assessed in two stages using the parent and teacher Conners' 3 ADHD index and the Diagnostic Interview Schedule for Children IV (DISC-IV). ASD symptoms were identified using the Social Communication Questionnaire (SCQ). Unadjusted and adjusted linear and logistic regression examined continuous and categorical outcomes, respectively. Children with ADHD had more ASD symptoms than non-ADHD controls (adjusted mean difference = 4.0, 95% confidence interval (CI) 2.8; 5.3, p  < 0.001, effect size = 0.7). Boys with ADHD had greater ASD symptom severity than girls with ADHD (adjusted mean difference = 2.9, 95% CI 0.8; 5.2, p  = 0.01, effect size = 0.4). Greater ADHD symptom severity was associated with greater ASD symptom severity (regression co-efficient = 1.6, 95% CI 1.2; 2.0, p  < 0.001). No differences were observed by ADHD subtype. Greater hyperactive/impulsive symptoms were associated with greater ASD symptoms (regression coefficient = 1.0; 95% CI 0.0; 2.0, p  = 0.04) however, this finding attenuated in adjusted analyses ( p  = 0.45). ASD symptoms are common in children with ADHD. It is important for clinicians to assess for ASD symptoms to ensure appropriate intervention.